Strategies in Translating English Sports Terms into Indonesian in Official Volleyball Rules - Tani S. Lestari (RIRAI Publisher, 2022)
Since most sports in Indonesia are imported products from other countries, it has resulted in a large number of Indonesian sports terms that are derived from other languages. This includes volleyball which originated in the United States. Therefore, a lot of volleyball terms in Indonesian are derived from English. This research focuses on the translation of sports terms from English into Indonesian in the translation of FIVB Official Volleyball Rules 2017-2020 into PBVSI Peraturan Resmi Bolavoli 2017-2020. Its aim is to identify the strategy used by the translator to find out how sports terms are translated from English into Indonesian. The research shows that three of Chesterman’s translation strategies, namely syntactic, semantic, and pragmatic strategies are used in the translation of Official Volleyball Rules from English into Indonesian. Of all 30 strategies from loan to other pragmatic strategies, 10 of them are used in the translation. The most frequently used strategies are unit shift, distribution change, loan, and calque. Meanwhile, the least used strategies are clause structure change, abstraction change, paraphrase, and cultural filtering.